BTT 304/3 – Genetic Engineering [Kejuruteraan Genetik]- January 2014 - PPSKJ, Pusat Pengajian Sains Kajihayat (2014)
First Semester Examination 2013/2014 Academic Session December 2013 / January 2014 Duration: 3 hours